Evaluation of a toolbox for the prevention of skin cancer among outdoor workers: an intervention study - de Boer, Florentine L.; Vreenegoor, Daisy; Twisk, Jos W. R.; van der Gragt, Jack J.; Rustemeyer, Thomas; Kezic, Sanja; van der Molen, Henk F. (Frontiers in Public Health, 2025)
IntroductionDue to ultraviolet radiation (UVR) exposure at work, outdoor workers face a higher risk of keratinocyte carcinoma (KC) than indoor workers. This study evaluates the short-term effectiveness of a sun-safety risk communication toolbox aimed to increase sun-safety behavior among male outdoor workers.MethodsThis parallel-controlled, non-randomized study included outdoor construction and arboricultural workers, recruited from five companies. Twenty-eight workers were assigned to the intervention group, where they received a preventive toolbox, while 26 workers were assigned to the control group. The toolbox included information on UVR health risks and preventive measures, as well as sunscreen provision. The primary outcome was internal UVR exposure, measured by the relative cis-urocanic acid (cUCA) levels in the stratum corneum (SC). SC samples were taken from two skin sites (cheek and neck) at baseline and 6 weeks. Secondary outcomes included sun-protective behavior, workplace encouragement, knowledge and attitude/motivation, all assessed using questionnaires.ResultsA difference in cUCA was found between groups with lower cUCA at the cheek (−0.065 (95% CI: −0.101 to −0.029)) and neck location (−0.032 (95% CI: −0.068–0.004)) for the intervention group. Reported sunscreen use significantly improved in the intervention compared with control group (difference between group (11.01 (95% CI: 2.04–20.10)). For other secondary outcomes no statistical differences between groups were found.ConclusionThe toolbox intervention led to a reduction of internal UVR exposure, consistent with a self-reported increase in sunscreen use, compared to no intervention. Future research should focus on the longer-term preventive effects of this type of toolbox following further development and evaluation.